Central European Functional Programming School: 6th Summer School, CEFP 2015, Budapest, Hungary, July 6-10, 2015, Revised Selected Papers - Zsok, Viktoria; Porkolab, Zoltan; Horvath, Zoltan (Lecture Notes in Computer Science, 2019)
This volume presents the revised lecture notes of selected talks given at the 6th Central European Functional Programming School, CEFP 2015, held in July 2015, in Budapest, Hungary.The 10 revised full papers presented were carefully reviewed and selected. The lectures covered a wide range of functional programming and C++ programming subjects.